Correlation between the willingness to compromise and effectiveness of regional regulations with green consumer behaviour - Lina Lina; Rita Retnowati; Yossa Istiadi (Indonesian Journal of Applied Environmental Studies, 2021)
The objective of this study is to find the correlation between the effectiveness level of regional regulations and willingness to compromise with green consumer behaviour. This research applied use correlational surveys with 100 samples housewives in Bogor city. The data analysis technique used is multiple regression. The result of this research shows that there is a very significant positive relationship that has a local regulation permit with green consumer behaviour, with a variable contribution of 56.2%. There is a very significant positive relationship between willingness to compromise with green consumer behaviour, with the variable contribution being 38.3%. There is a very significant positive relationship between the application of local regulations and the willingness to compromise together with green consumer behaviour, with the variable contribution being 57.9%. The functional relationship between the application of local regulations and willingness to compromise with the green consumer behaviour variable fulfills the regression equation Å¶12 = 21.866 + 0.404X1 + 0.214X2  and this relationship is significant.Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara tingkat efektivitas peraturan daerah dan kemauan berkompromi dengan perilaku konsumen hijau. Penelitian ini menggunakan metode survei korelasional dengan sampel 100 ibu rumah tangga di kota Bogor. Teknik analisis data yang digunakan adalah regresi berganda. Hasil penelitian menunjukkan bahwa terdapat hubungan positif yang sangat signifikan antara izin peraturan daerah dengan perilaku konsumen hijau, dengan kontribusi variabel sebesar 56,2%. Terdapat hubungan positif yang sangat signifikan antara kesediaan berkompromi dengan perilaku konsumen hijau, dengan kontribusi variabel sebesar 38,3%. Terdapat hubungan positif yang sangat signifikan antara penerapan peraturan daerah dengan kemauan berkompromi dengan perilaku konsumen hijau, dengan kontribusi variabel sebesar 57,9%. Hubungan fungsional antara penerapan peraturan daerah dan kemauan berkompromi dengan variabel perilaku konsumen hijau memenuhi persamaan regresi 12 = 21,866 + 0,404X1 + 0,214X2 dan hubungan ini signifikan.